2013
DOI: 10.1111/jeb.12295
|View full text |Cite
|
Sign up to set email alerts
|

Selection of trait combinations through bee and fly visitation to flowers of Polemonium foliosissimum

Abstract: Pollinators are known to exert natural selection on floral traits, but the extent to which combinations of floral traits are subject to correlational selection (nonadditive effects of two traits on fitness) is not well understood. Over two years, we used phenotypic manipulations of plant traits to test for effects of flower colour, flower shape and their interaction on rates of pollinator visitation to Polemonium foliosissimum. We also tested for correlational selection based on weighting visitation by the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Hummingbirds favored wide corolla tube width and vertical presentation of the flowers, neither of which is found in S. virginica, but this preference was trait context dependent. Association of contrary characters states with greater pollinator visitation has also been documented in at least one other study utilizing two trait manipulations (Campbell et al 2014). The question is: why would present-day S. virginica exhibit traits that do not consistently improve attraction?…”
Section: Contrary Hummingbird Preferencementioning
confidence: 61%
See 2 more Smart Citations
“…Hummingbirds favored wide corolla tube width and vertical presentation of the flowers, neither of which is found in S. virginica, but this preference was trait context dependent. Association of contrary characters states with greater pollinator visitation has also been documented in at least one other study utilizing two trait manipulations (Campbell et al 2014). The question is: why would present-day S. virginica exhibit traits that do not consistently improve attraction?…”
Section: Contrary Hummingbird Preferencementioning
confidence: 61%
“…The microevolutionary equivalent of our experiment (here we manipulated traits across macroevolutionary scales) is quantifying the role of correlational selection to phenotypic selection, that is, the detection of selection to increase trait covariance. In the just cited references and other phenotypic selection studies, there is little evidence of correlational selection acting on the flower (Sletvold et al 2012;Kulbaba and Worley 2012), and when correlational selection is detected, it is often limited to a subset of two-trait interactions (Conner et al 1996a,b;Valdivia and Niemeyer 2006;reviewed in Campbell 2009;Nattero et al 2010;Vanhoenacker et al 2010;Agren 2010, 2010;Bartkowski and Johnston 2012;Campbell et al 2014). However, when dimension reduction techniques are used, for example canonical analysis (Reynolds et al 2010a, b), selection acting on trait interactions is often observed.…”
Section: Of Phenotypic Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollinators may exert selection not only on single floral traits but also on combinations of traits, that is, correlational selection. In particular, correlational selection is expected when one trait influences the rate of pollinator visitation and a second trait influences pollinator effectiveness per visit, because pollination success will depend on the product of these two components (Sletvold & Agren, 2011;Campbell et al, 2014). In the orchid Dactylorhiza lapponica, phenotypic manipulations documented nonadditive effects on reproductive success of floral display and spur length, a trait affecting pollination efficiency (Sletvold & Agren, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, because Hylemya does not pollinate the flowers on which it oviposits, larvae will perish if their host flower is not pollinated. Thus the most important cues for Hylemya may be those used by pollinators such as corolla size (Brody, ) or a combination of floral traits (Campbell et al , ). Interestingly, although petal size and sepal size were not correlated here on P. foliosissimum , they are correlated on I. aggregata , the alternative host for Hylemya (Brody, ; Campbell et al , ).…”
Section: Discussionmentioning
confidence: 99%